Can climate policy promote high-quality development of enterprises? Evidence from China - Cai, Xiaoshan; Huang, Yiting; Ying, Sammy Xiaoyan; Chen, He (Frontiers in Environmental Science, 2023)
Climate policy is of great importance for China’s climate goals of achieving peak carbon emissions by 2030 and carbon neutrality by 2060. However, whether the climate policy can consider economic performance and achieve high-quality economic development remains to be tested. Based on the perspective of high-quality economic development, this paper takes three batches of low carbon city pilot in China as a quasi-natural experiment, and uses Time-varying Difference-in-Differences to examine the impact of climate policy on high-quality development of enterprises based on the panel data of 333 cities in China from 2007 to 2020. The findings show that the current climate policy in general does not promote the high-quality development of enterprises, when comprehensively considering the gradually strengthening regulation intensity of pilot policy in batches. The result holds after a battery of robustness tests. Further analysis shows that the economic mechanism behind it lies in that environmental regulation arising from the climate policy only triggers the “compliance cost effect” instead of the “innovation offset effect”. It also finds that the inhibition effect of climate policy on high-quality development is more pronounced for non-state-owned enterprises, small-scale enterprises and the sample with strong local environmental law enforcement. The findings of this paper would complement the existing theoretical research via evaluating the effectiveness of China's current low carbon policy at the micro level, and provide policy implications to the implementation of future climate policies so as to mitigate climate change and achieve high-quality economic development. In addition, our estimation strategy can serve as a scientific reference for similar studies in other developing countries.